E-D2CARP: a joint path and spectrum diversity based routing protocol with an optimized path selection for cognitive radio ad hoc networks - Che-Aron, Zamree; Hassan Abdalla Hashim, Aisha; Hassan, Wan Haslina; Abdullah, Khaizuran; Rahman, Muhammad ArafatuR (IEEE, 2014)
Cognitive Radio (CR) is a new paradigm which offers a viable solution to deal with the spectrum shortage problem and enhance the spectrum utilization. In Cognitive Radio Ad Hoc Networks (CRAHNs), data routing is one of the most challenging tasks due to frequent topology changes and intermittent connectivity caused by the activity of Primary Users (PUs). This paper proposes a joint path and spectrum diversity based routing protocol with an optimized path selection for CRAHNs, referred to the Enhanced Dual Diversity Cognitive Ad-hoc Routing Protocol (E-D2CARP). The Expected Path Delay (EPD) routing metric used in the protocol for path decision is also introduced. The protocol utilizes the joint path and spectrum diversity and circumvents the PU regions during path establishment phase in order to make the transmission path less vulnerable to the impact of PU activities and provide efficient route recovery in presence of path failures resulting from PU activities. The performance evaluations are conducted through simulations using the NS-2 simulator. Simulation results obviously demonstrate that the E-D2CARP can achieve better performance in terms of average throughput, packet loss, average end-to-end delay, and average jitter as compared to the recently proposed D2CARP protocol in identical scenarios.